AB0036 Different Regimens of Vitamin D Supplementation Determine an Effect on Phenotype and Function of T Cells in Patients with Systemic Lupus Erythematosus. Results from A Prospective Study. (10th June 2014) - Piantoni, S.; Zanola, A.; Andreoli, L.; Dall'Ara, F.; Scarsi, M.; Tincani, A.
Abstract : Background: In addition to the classical role on bone metabolism, recent studies highlight that vitamin D (VD) may have an immunomodulatory action on T cells, inhibiting Th-1 and Th-17 response and enhancing Th-2 and T-regulatory (Treg) function. After repeated antigenic presentation, T cells undergo different functional and phenotypical modifications, leading to the differentiation into highly experienced memory T cells (CD45RA+CCR7-) and to the down-modulation of CD28. It may lead to the peripheral expansion of the CD28- T cells, a subpopulation with peculiar effector activities (high g-IFN production) [1]. Systemic Lupus Erythematosus (SLE) is an autoimmune disease in which activation of autoreactive T and B lymphocytes and alteration of Treg functionality may have a pathogenic role [2]. A great prevalence of VD insufficiency has been described in SLE patients (pts), probably due to the low direct sunlight exposition. Objectives: To study the effect of VD supplementation on the circulating levels of different T-cells subsets and on cytokines production in patients with SLE. Methods: 51 female SLE pts with a clinically quiescent but serologically active disease were enrolled. 33 pts were supplemented with an intensive regimen (IR) of colecalciferol (300.000UI for the first month and 50.000UI/monthly as maintenance), whereas 18 pts were supplemented with a standard regimen (SR) (25.000UI monthly). Phenotypic analysis of peripheral T lymphocyte and the intracytoplasmatic production of IL-4 and g-IFN from peripheral blood mononuclear cells was evaluated by flow-cytometry. Results: After 12 months of treatment, a significant increase in the percentage of peripheral induced Treg cells (CD25highCD127lowCCR7-) was observed independently from the regimen of supplementation and a gain of recent thymic emigrants (RTE) Treg cells (CD25highCD127lowCD31+) was detected in pts of IR (table 1 ). We also observed an increase in the total amount of circulating CD4+CD45RA+CCR7- T cells, whereas a significative reduction of the CD8+CD28- T cells in SLE pts on SR was seen (table 1 ). In the IR group of patients evaluated for cytokines production (n=8), a reduction of g-IFN/IL-4 (from 12.1 to 3.2; p=0.01) among CD8+ T cells was detected. Conclusions: VD may have immunomodulatory properties on T cells, enhancing an increase of different subpopulations of Treg cells and promoting the production of Th2 cytokines. References: Strioga M. Immunology 2011; 134 (1): 17-32; Terrier B et al. Arthritis Res Ther 2012; 14: R221. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4400